-2y-6=-14

Simple and best practice solution for -2y-6=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y-6=-14 equation:


Simplifying
-2y + -6 = -14

Reorder the terms:
-6 + -2y = -14

Solving
-6 + -2y = -14

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -2y = -14 + 6

Combine like terms: -6 + 6 = 0
0 + -2y = -14 + 6
-2y = -14 + 6

Combine like terms: -14 + 6 = -8
-2y = -8

Divide each side by '-2'.
y = 4

Simplifying
y = 4

See similar equations:

| 4x+1=149 | | (x+1)-(x^2+1)=0 | | 8/12x9/12 | | a-1.5(a+8)=4.5 | | -4+d=3 | | 0=q-14 | | lgx=-5 | | 8z+15=3z-20 | | y/6=-1 | | 7w+4=2(7w-5) | | (7x^2+17x+13)-(12x^2+10x+4)=0 | | 3y-4x=6Fory | | -3(r+7)=-55 | | 7y+2x=5 | | x=5y+8.75 | | 3(m+31)=33 | | (x+1)-(x^2+2)=0 | | 14=-7/9v | | 7t-11=24 | | 3x^2-2y^3+6x=0 | | -5(1+6x)+3x=21-x | | 4x-9=6x-21 | | X+y+(x+41)=887 | | -2/3n=32/9 | | y=1000(1.75)t | | 4x-9+4y+8=180 | | -250x+100=600 | | 2-6z=8 | | 2x/3x=5 | | X-5/y-4 | | 16x-10x+9=99x-30 | | 10ab/4b |

Equations solver categories